Detrital zircon geochronology and provenance of the Chubut Group in the northeast of Patagonia, Argentina - Navarro, Edgardo Luis (2015)
The Chubut Group constitutes the most widespread sedimentary unit in NE Patagonia, characterized by variable-energy fluvial deposits. U–Pb analysis of detrital zircons from two sections of the Chubut Group constraint the age of the oldest sedimentary rocks in the northeast of the Somuncurá – Cañadón Asfalto Basin. In the Cañadón Williams area, at San Jorge section, 20 km NW of Telsen locality, dating of 56 detrital zircons from a medium to coarse sandstone indicated a maximum depositional age of 109 ± 1 Ma (n = 4). These sandstones were interpreted to represent shallow channels, associated with a lacustrine system. In the Telsen locality, a laser ablation analysis of 115 detrital zircons from a medium to coarse-grained sandstone, from fluvial channel facies, yielded a maximum depositional age of ca. 106 ± 1 Ma (n = 8). Both ages are consistent with volcanic events of the Barremian to Albian age in the central Patagonian Andes Region. Cathodoluminescence images of zircons from the San Jorge sample suggest an igneous origin, which is further supported by Th/U values above 0.5 in most of the grains. The distribution of the statistical modes of the main age populations of detrital zircons for the two samples [182, 185 and 189 Ma for Telsen sample (T2S) and 181 ± 1 Ma for San Jorge sample (SJS)] matches the age of the volcanic Marifil Formation. The rocks of the Marifil Formation of these ages are exposed NE to SE of the study area. The abundance of zircons of similar Jurassic ages (n = 52 for SJS and n = 105 for T2S) and the external morphology of the zircons in the sample SJS, implies a close proximity of the source area. Suggestion that the Marifil Formation was the main provenance source is also supported by northeast–southeasterly paleocurrents measured at the San Jorge and Telsen sections.